Cyberbullying among college students with disabilities. (April 2016) - Kowalski, Robin M.; Morgan, Chad A.; Drake-Lavelle, Kelan; Allison, Brooke
Abstract: Cyberbullying has received increasing attention in recent years. However, the majority of this research has focused on children in middle school and on neurotypical youth, to the omission of people with disabilities. The current study, however, examines cyberbullying as it occurs among college students with and without disabilities. Two hundred five students completed a survey examining their experiences with cyberbullying, along with measures of predictor and outcome variables theorized to be related to cyberbullying. The results revealed that, as with traditional bullying, students with disabilities are at particular risk for cyberbullying victimization. Predictors of victimization included traditional bullying victimization, Internet use, and the noticeability of the disability. Outcomes of cyberbullying victimization (e.g., low self-esteem, high depression) appear to be particularly pronounced for individuals with disabilities. Highlights: Cyberbullying among college students with disabilities is examined. Students with disabilities at particular risk for cyberbullying victimization. Traditional bullying victimization and disability noticeability predictors of victimization.